Electronic Customer Relationship Management Systems in E-Commerce Platforms: Exploring the Antecedents of Technology Acceptance and Customer Satisfaction - Iyus Rustandi; Ida Hindarsah; Maun Jamaludin (Media Ekonomi dan Manajemen, 2024)
This paper undertakes a comprehensive analysis of the cutting-edge maneuvers in Electronic Customer Relationship Management e-CRM in an e-commerce context, encompassing four significant categories: e-CRM, cost, technology acceptance, and customer satisfaction. It also evaluates the construct developments in these four categories. To assess the effectiveness and accuracy of the measurement model, the method of Structural Equation Modeling was utilized. Gathered data from 167 e-commerce sellers in Bandung, the results showed that e-CRM performance relied heavily on the ability of infrastructure, ease of use, and e-learning systems. The development and integration of these factors led to a positive effect on the effectiveness of the e-CRM. In addition, the findings underscored that customer expenses had a favorable influence on customer relationship performance. Consequently, this relationship performance led to an enhancement in the overall effectiveness of the e-CRM in e-commerce. A managerial implication for each category is also provided, along with suggestions for future research and directions.